Harimau Sumatra (Panthera Tigris Sumatrae): Dari Ekspansi Kolonial Hingga Perburuan di Sumatra Awal Abad XX - Albertus Hutagalung; Gusti Asnan (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This study aims to reconstruct the activities of colonial expansion and tiger hunting in Sumatra, focusing on the motives, methods, and impacts on the tiger population and local communities. The primary objective of this research is to understand the various factors driving tiger hunting and how these activities affect the tiger population. The research methods include literature review and historical document analysis, encompassing colonial reports, archives, and photographs using a narrativism approach, a methodology in the philosophy of history used to reconstruct the past. The findings indicate that tiger hunting was driven not only by the need to protect humans but also by colonial expansion motives and as a symbol of social status. Furthermore, intensive hunting caused a significant decline in the tiger population. These wild animals have become victims of colonial modernization ambitions. Hunting, driven by infrastructure development, has deprived them of their habitat and threatened their survival.